Human Leukocyte Antigen (HLA) in Korean patients with Autoimmune Thyroid Diseases - Huh, Kap Bum (Korean J Intern Med, 1986)
In previous studies, there has been evidence of different allelic associations with a particular disease among various ethnic groups. The present study was done to investigate the associations between HLA and autoimmune thyroid diseases in the Korean. We found no association between Graves’ disease and HLA-B8 or -B35. However, increased frequencies of HLA-A11 and -DRw8, and the decreased frequencies of HLA-A10 and B12 were found in patients with Graves’ disease. In the cases of Hashimoto’s disease, the frequencies of HLA-A2 and -DRw8 were found to be significantly increased and the frequency of HLA-DRw6y decreased. These data indicate that the association between autoimmune thyroid disease and HLA in the Korean would appear to be different from that in most other racial groups, including Caucasians, Japanese and Chinese.